Alone at home: The impact of social distancing on norm-consistent behavior - Sabrina Jeworrek; Joschka Waibel (Halle Institute for Economic Research (IWH), 2021)
Around the globe, the COVID-19 pandemic has turned daily live upside down since social distancing is probably the most effective means of containing the virus until herd immunity is reached. Social norms have been shown to be an important determinant of social distancing behaviors. By conducting two experiments and using the priming method to manipulate social isolation recollections, we study whether social distancing has in turn affected norms of prosociality and norm compliance. The normative expectations of what behaviors others would approve or disapprove in our experimental setting did not change. Looking at actual behavior, however, we find that persistent social distancing indeed caused a decline in prosociality - even after the relaxation of social distancing rules and in times of optimism. At the same time, our results contain some good news since subjects seem still to care for norms and become more prosocial once again after we draw their attention to the empirical norm of how others have previously behaved in a similar situation.
Keywords: C91; D64; D91; H12; 330; COVID-19; human behavior; norm compliance; post-COVID; priming; pro-sociality; social expectations